The Question of Legitimizing Law in Adolf Reinach’s Phenomenology - Bekrycht, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
When speaking about legitimizing law we can mainly mean analysis which concerns metaphysical justification for what is called the phenomenon of law. From the metaphysical point of view, the justification of law means indicating the foundation of its existence. It is about seeking (indicating) an esse (essence) basis of law, in line with the task set by the metaphysical analysis, namely seeking an answer to the question: Why does object X exist? And in the answer, there will appear a formula indicating the final reasons for its existence (ratio essendi). The same ideas that we can find in Adolf Reinach’s principal work, The Apriori Foundations of the Civil Law, provide a possibility of better understanding this important issue of legal philosophy, namely the question of legitimizing law (justifying law). The aim of this article is to present that argument.